Personal Branding in the Supply Chain Sector of the Establishment of Medco Energi’s Corporate Culture - Suraya Mansur; Pujitriasih Prabandari (International Journal of Supply Chain Management, 2020)
Abstract-This study analyzes the influence of Arifin Panigoro’s personal branding towards in the supply chain management sector for the the establishment of Medco Energi’s Corporate Culture. Arifin Panigoro was the founder of PT. Meta Epsi Drilling Company (abbreviated as ‘Medco’), an Indonesian Oil Well Drilling Service Company that has been continuously developed into an international scale company, which better known as Medco Energi. It is believed that the values held by Arifin Panigoro have contributed to the company’s development and growth to become the current Medco Energi. Arifin puts the following 9 principles as his priority in doing business; intuition, equality, honesty, confidence, networks, responsible, human resources, innovation, and care. These 9 principles were then being compacted into 4 major values known as P.E.T.I (Peduli—Care, Etik—Ethics, Terbuka—Open, Inovasi—Innovation). By using a qualitative research approach through a descriptive case study method, this study gathers 8 informants that got selected through purposive sampling procedure. The result shows that the solidness and authenticity of Arifin Panigoro's personal branding were constructed naturally and unintentionally throughout his long journey in doing business. There was no measurement to his personal branding performance, yet subsequently has a strong connection towards Medco Energi’s corporate culture. The study concludes that Arifin Panigoro’s figure represents worker, entrepreneur, and leader with solid and authentic personal branding that has been proven from time to time. Along the process of its development, Arifin Panigoro’s personal branding has been successfully documented and capitalized by MedcoEnergi that resulted the forming of P.E.T.I concept (which is more normative, concise, and pragmatic) and extended with the Arifin Panigoro’s 9 Business Principles concept (which is more personal). Both concepts are the success indicators of Arifin Panigoro’s personal branding in the establishment of Medco Energi’s corporate culture.